Microring resonator (MRR) optical systems applied to enhance the soliton communications - Amiri, I. S. (Nova Science Publishers, Inc., 2015)
A spectrum of light over a broad range can be generated, thus solitons can be utilized to generate chaotic filter features when spreading within nonlinear microring resonators (MRRs). We propose a systems of MRRs that uses localized soliton pulses to form the optical communication signals. This method uses nonlinear behaviours of light applicable for soliton transmission. Optical carrier generation is the basic building block for communication systems in the optical domain. One important aspect of the MRR system is that tuning of the system parameters allows for desired soliton carriers with specific key characteristics. The normalized output of the light field is defined by the ratio between the output and input fields. The results demonstrate optical soliton pulses localized within the MRRs system with 20,000 roundtrips. A frequency soliton pulse can be formed and trapped within the panda ring resonator system with suitable ring parameters. The throughput output (Eth) shows localised soliton pulses with full width at half maximum (FWHM) and free spectral range (FSR) of 5 MHz and 2 GHz, respectively, where soliton pulses at frequencies of 50 and 52 GHz are generated. The drop output (Ed) shows pulses with FWHM and FSR of 10 MHz 2 GHz. The efficiency of this system can be evaluated by the output solitonic carrier signal generated by the MRRs.